AB0986 A Systematic Screening of Comorbidities by The Rheumatologist in Inflammatory Rheumatisms Impacts Chronic Disease Care. (15th July 2016) - Tubery, A.; Fesler, P.; Du Cailar, G.; Morel, J.; Bousquet, J.; Combe, B.; Daien, C.
Abstract : Background: In chronic inflammatory rheumatic diseases, comorbidities such as cardiovascular disease and infections are sub-optimally managed. EULAR recently developed points to consider to collect and report comorbidities and up-dated recommendation on cardiovascular disease evaluation. Objectives: We developed a systematic screening of comorbidities in out-patient daily clinic of the Rheumatology department in Montpellier University Hospital. Our objective was to evaluate the impact of such a screening. Methods: The assessment included rheumatism evaluation, cardiovascular risk factors and diseases, osteoporosis, chronic respiratory disease screenings, check-up of vaccine calendar and recommended neoplasia screenings. This was a medical and paramedics evaluation (physicians, nurses and physiotherapists) including anthropometric and blood pressure measures, blood tests, vessel ultrasound, echocardiography, self-questionnaires, spirometry and bone mineral density. Therapeutic changes for rheumatism and osteoporosis were performed during hospitalization whereas those related to cardiovascular and lung diseases were addressed to the general practitioner. Three months later, patients were called and the application of recommendation evaluated. Results: 200 patients had a systematic chronic disease screening with 78.5% (n=157) of RA, 18.5% (n=37) of spondyloarthritis, and 3% (n=6) of other diseases. The mean rheumatism duration was 14±9 years, the mean age was 59±11 years. Unknown or uncontrolled hypertension was diagnosed in 20.5% (n=41); LDL above the recommended target in 63% (n=126); unknown diabetes in 3.5% (n=7) of the patients and uncontrolled diabetes in 4 of the diabetic patients (23.5%). Moreover, 7 patients had low systolic pression index (3.5%), 10 had a significant supra-aortic vessel stenosis of more than 50% (5%) and 18 had significant abnormalities in echocardiography (9%). An obstructive respiratory syndrome was found in 20 patients (10%) and sleep apnea syndrome in 78 patients (39%). An anti-osteoporosis drug was prescribed in 11% (n=22) patients. The update of the vaccinations and the neoplasia screenings were proposed for 52.5% (n=105) and 39% (n=79) patients respectively. 144 patients received physiotherapy or occupational therapy advice for the management of their rheumatologic disease (72%). At 3 months, patients declared to have followed the recommendations in 50 to 75% of the cases, the items related to rheumatology being more often applied. Conclusions: A daily hospitalisation for comorbidities screening seems profitable with many abnormalities discovered in patients yet monitored regularly at hospital. The effective implementation of the proposed or prescribed measures is being assessed. Disclosure of Interest: None declared